Kitman Labs Performance Intelligence Research Initiative: A survey to bring research on the field - Buchheit, M.; McHugh, D.; Smith, S. (Sport Performance & Science Reports, 2021)
There is no shortage of topics when it comes to conducting research in Sports Science. However, whether investigations are part of typical academic research programs (e.g., Masters, PhDs) or industrydriven (e.g., Club Research and Development departments, Technology companies), their ability to transfer into the field of (elite) sports and improve substantially current practices is often limited [1-6]. This disconnection between research and practices can be attributed to the important publication constraints, that sometimes force researchers to partially compromise their work to get their paper suitable for publication (e.g., using overly-controlled study designs, favoring mean vs individual responses, cherry-picking data to have `results`) [7, 8]. The lack of clear research focus on the most relevant topics for practitioners is also often suggested as one of the first limitations for research to have an impact in the field of elite sport [1, 8]. Indeed, without clear connections between both academic and practitioner worlds [6], it is difficult for the right questions to land on researchers` desks, and appropriate research to be conducted. The consequence of this is that often, researchers are busy building the spaceship to land on the moon, while no one has asked them to go.